Effects of Dinotefuran on Brain miRNA Expression Profiles in Young Adult Honey Bees (Hymenopptera: Apidae). Issue 1 (5th January 2021) - Huang, Minjie; Dong, Jie; Guo, Haikun; Wang, Deqian
Abstract: Honey bees are important pollinators of wild plants and crops. MicroRNAs (miRNAs) are endogenous regulators of gene expression. In this study, we initially determined that the lethal concentration 50 (LC50 ) of dinotefuran was 0.773 mg/l. Then, the expression profiles and differentially expressed miRNAs (DE miRNAs) in honey bee brains after 1, 5, and 10 d of treatment with the lethal concentration 10 (LC10 ) of dinotefuran were explored via deep small-RNA sequencing and bioinformatics. In total, 2, 23, and 27 DE miRNAs were identified after persistent exposure to the LC10 of dinotefuran for 1, 5, and 10 d, respectively. Some abundant miRNAs, such as ame-miR-375-3p, ame-miR-281-5p, ame-miR-3786-3p, ame-miR-10-5p, and ame-miR-6037-3p, were extremely significantly differentially expressed. Enrichment analysis suggested that the candidate target genes of the DE miRNAs are involved in the regulation of biological processes, cellular processes, and behaviors. These results expand our understanding of the regulatory roles of miRNAs in honey bee Apis mellifera (Hymenopptera: Apidae) responses to neonicotinoid insecticides and facilitate further studies on the functions of miRNAs in honey bees. Graphical Abstract: